(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Present study explored the influence of stretching constraint in addition with inclusion of energy. An analytical solution for the system of non-linear equations of motion is worked out by adopting Homotopy Perturbation method (HPM). Physical and graphical reflections various parameters are demonstrated in the present problem. Utility of this model has been perceived in diverse industrial and chemical processes. 2010 AMS subject classification: 76W05